Mean sea‐level variability along the northeast American Atlantic coast and the roles of the wind and the overturning circulation. Issue 12 (29th December 2014) - Woodworth, Philip L.; Maqueda, Miguel Á. Morales; Roussenov, Vassil M.; Williams, Richard G.; Hughes, Chris W.
Abstract The variability in mean sea level (MSL) during 1950–2009 along the northeast American Atlantic coast north of Cape Hatteras has been studied, using data from tide gauges and satellite altimetry and information from the Liverpool/Hadley Centre (LHC) ocean model, thereby providing new insights into the spatial and temporal scales of the variability. Although a relationship between sea level and the overturning circulation can be identified (an increase of approximately 1.5 cm in MSL for a decrease of 1 Sv in overturning transport), it is the effect of the nearshore wind forcing on the shelf that is found to dominate the interannual sea‐level variability. In particular, winds are found to be capable of producing low‐frequency changes in MSL ("accelerations") in a narrow coastal band, comparable to those observed by the tide gauges. Evidence is presented supporting the idea of a "'common mode" of spatially coherent low‐frequency MSL variability, both to the north and south of Cape Hatteras and throughout the northwest Atlantic, which is associated with large spatial‐scale density changes from year to year.